Modeling of two-dimensional unsteady gas flows in self-heating solid waste dumps - Levin, Vladimir Alexeevich; Lutsenko, Nikolay Anatolievich (Computational Continuum Mechanics, 2011)
A mathematical model and a numerical method have been developed for the investigation of unsteady gas flows in self-heating solid waste dumps when the detailed chemical kinetics is neglected. Using numerical experiments, vortex-type flows in the heat source and in its vicinity have been revealed. The vortex-type flows can make the heat removal from the considered object significantly worse. The complete attenuation of the heat source, the steady-state regime of self-heating or the unlimited heating of the porous objects are shown to be established depending on the initial and boundary conditions and the problem parameters.